Theology, comedy, politics - Pound, Marcus (Dispatches (Minneapolis, Minn.), 2019)
What is the relevance of comedy for the global crises of late-modernity and the theological critique thereof? This book develops recent philosophical, anthropological, and psychoanalytical studies of humor to develop a theology of comedy. It argues that comedy only participates in the divine, but that it should inform our liturgical, sacramental, and ecclesial life if we are to respond to the postmodern age in which having fun is an ideological imperative of market forces.